Dissipation by transfer and its influence on fusion - Colucci Giulia; Trzcińska Agnieszka; Wen Pei Wei; Piasecki Ernest (EPJ Web of Conferences)
A new version of the CCQEL code has been developed by upgrading the method of coupling of transfer channels during fusion and backscattering processes. In particular, the number of transfer reactions included has been increased and the dependence of the strength of transfer coupling on the transferred particle and experimental Q-value distribution was introduced. The upgraded code was employed for the investigation of the influence of transfer on the smoothing of the measured quasielastic barrier distribution (Dqe) of the 24Mg + 92Zr and 20Ne + 208Pb systems and found interesting discrepancies with respect to the standard approximations. The study with the upgraded code indicates the transfer responsible for generating strongly excited targets as the leading cause of the smearing of the barrier distribution, even in the case of negative ground state to ground state Q value (Qgg). The smoothing observed in the barrier distribution is dominated rather by one neutron transfer, despite the negative Qgg value for this reaction and the positive Qgg value for two-neutron transfer. Of particular interest is the case of the 20Ne + 208Pb, where the smoothing of the Dqe is mainly influenced by the one neutron pick-up at the beam energy above the barrier, while the one neutron pick-up and one proton stripping transfers are dominant for lower beam energy. These results highlight the importance of the transfer coupling dependence on the experimental Q-value distribution and, consequently, on the projectile kinetic energy.